2019
DOI: 10.3389/fimmu.2019.00260
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Mucosal-Associated Invariant T Cells in a Large Cohort of Healthy Chinese Individuals From Newborn to Elderly

Abstract: Mucosal-associated invariant T (MAIT) cells, which are enriched in human blood and express a semi-invariant TCR chain, play important roles in conditions such as infectious diseases and cancer. The influence of age on levels and functional characteristics of circulating MAIT cells have not been fully addressed. Here we have collected blood samples from a large cohort of healthy Chinese individuals from newborn (cord blood) to the elderly and assessed the levels of circulating MAIT cells as well as their phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 40 publications
11
55
0
Order By: Relevance
“…Of note, one person with diabetes had a significant proportion of CD4 + MAIT cells (47.2%). Such a high frequency of circulating CD4 + MAIT cells is not uncommon and has been reported before in healthy individuals (32). No significant differences in iNKT or Vδ2 + T cell subsets were observed (Figures 1C,D).…”
Section: Metabolic Disease-associated Differences In Ex Vivo Activatisupporting
confidence: 83%
“…Of note, one person with diabetes had a significant proportion of CD4 + MAIT cells (47.2%). Such a high frequency of circulating CD4 + MAIT cells is not uncommon and has been reported before in healthy individuals (32). No significant differences in iNKT or Vδ2 + T cell subsets were observed (Figures 1C,D).…”
Section: Metabolic Disease-associated Differences In Ex Vivo Activatisupporting
confidence: 83%
“…However, the reason for this change is less clear. Some studies found the peripheral MAIT cells were age-related and changed with age [48][49][50]. The most common explanation for the reduction was attributed to the apoptosis [17,51].…”
Section: Ivyspringmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted December 1, 2020. ; https://doi.org/10.1101/2020.12.01.407148 doi: bioRxiv preprint setting. This difference can be explained by the rate of physiological aging-related attrition of MAIT cells that is substantially less pronounced in female blood (40)(41)(42). The resultant higher frequencies in circulation enabled us to readily uncover the precipitous percentage drop we saw with MAIT cells relative to exposed/infected females.…”
Section: Discussionmentioning
confidence: 94%